2011
DOI: 10.1097/jsm.0b013e318218acdd
|View full text |Cite
|
Sign up to set email alerts
|

Rodeo Catastrophic Injuries and Registry: Initial Retrospective and Prospective Report

Abstract: Thoracic compression mechanisms of injury are most pervasive and likely to be fatal in rodeo and bull riding. It is unknown whether rodeo protective vests have a protective effect in reducing catastrophic and fatal injuries. On the contrary, helmet use in bull riding and rodeo events seems to have a protective effect in reducing both catastrophic injury and fatality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 7 publications
1
28
0
1
Order By: Relevance
“…Three patients identified in the general animal-riding population were wearing a helmet and did not sustain a TBI. Many other studies suggest that helmet use in rodeo events can reduce incidents of head injury and fatality (Butterwick et al, 2011; Havlik, 2010; Ross et al, 2010; Worley, 2010). This study supported our hypothesis of outcomes correlated to the nonuse of protective headgear during animal-riding accidents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three patients identified in the general animal-riding population were wearing a helmet and did not sustain a TBI. Many other studies suggest that helmet use in rodeo events can reduce incidents of head injury and fatality (Butterwick et al, 2011; Havlik, 2010; Ross et al, 2010; Worley, 2010). This study supported our hypothesis of outcomes correlated to the nonuse of protective headgear during animal-riding accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Various literature also supported the use of an educational injury prevention program that includes head protection to decrease the incidences of TBI and lead to a better quality of life (Butterwick et al, 2011; Davidson et al, 2015; Hasler et al, 2011; Ross et al, 2010). One of the most interesting findings in our study was related to the high number of incidents found in the female pediatric population and these occurrences were also found in other studies (Davidson et al, 2015; Hasler et al, 2011; Havlik, 2010; Worley, 2010), leading us to conclude that our findings were consistent among similar cohorts and locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to reduce injury by wearing protective vests have been adopted by rodeo sanctioning organizations, though few data are available to prove they significantly reduce the incidence of catastrophic thoracic injury. 13 Utilization of protective thoracic vests over the past 20 years was believed to have reduced the severity of compression thoracic injury by dispersing and absorbing the impact of a traumatic blow. 14 This belief was based on anecdotal evidence, and did little to dispel the controversy surrounding whether vests provide adequate protection, since deaths still were reported when vests are used.…”
Section: Discussionmentioning
confidence: 99%
“…The NCCSIR has collected injury data since 1965 on deaths and disability from brain and/or spinal cord injury attributed to high school and college sports participation in the Unites States. However, despite the real and perceived risks and increasing attention to catastrophic injuries in AES, no organization with the exception of the Rodeo Catastrophic Injury Registry (in operation during 1989-2009) has systematically collected such information nationally (Butterwick, Lafave, Lau, & Freeman, 2011).…”
Section: Clinical Outcomementioning
confidence: 99%